ECONOMIC, SOCIAL AND LIVING CONDITIONS OF WORKERS OF GOLD JEWELLERY INDUSTRY IN THRISSUR DISTRICT KERALA - Kanakachandran C.R (MIRROR, 2018)
The Gold business in Thrissur is a major revenue earner for the economy of Kerala, India. About 500 kg of gold jewellery is manufactured every year in state, the majority of which is done in Thrissur, making the city a hub of gold business and gold jewellery manufacturing in Kerala and South India. All major jewellery groups in Kerala have manufacturing facility in Thrissur. About 90 tones of gold was being used annually in Kerala for manufacturing of ornaments daily .This study aims to develop a profile of Economic, Social and Living Conditions of Workers of Gold Jewellery Industry in Thrissur District. This paper attempts to identify the social status of the labours and their economic condition and living standards. By assessing these, develop a profile of labours engaged in gold ornament manufacturing sectors in Thrissur district. The study also aims at giving some suggestions to improve the living condition of gold workers. Gold ornament manufacturing sector is unorganized in nature. A number of people are engaged in this sector as labours. Jewellery sector has been one of the fastest growing sectors in India in the past few years. The sector has gained global popularity because of its talented craftsman, its superior practices in cutting and polishing gold and its cost- efficiencies.